An Immobilized Enzyme Reactor for Spatiotemporal Control over Reaction Products. Issue 31 (3rd July 2018) - Grant, Jennifer; Modica, Justin A.; Roll, Juliet; Perkovich, Paul; Mrksich, Milan
Abstract: This paper describes a microfluidic chip wherein the position and order of two immobilized enzymes affects the type and quantity of reaction products in the flowing fluid. Assembly of the chip is based on a self‐assembled monolayer presenting two orthogonal covalent capture ligands that immobilize their respective fusion enzyme. A thiol‐tagged substrate is flowed over a region presenting the first enzyme—which generates a product that is efficiently transferred to the second enzyme—and the second enzyme's product binds to an adjacent thiol capture site on the chip. The amount of the three possible reaction products is quantified directly on the chip using self‐assembled monolayers for matrix‐assisted laser desorption/ionization mass spectrometry, revealing that the same microsystem can be spatiotemporally arranged to produce different products depending on the device design. This work allows for optimizing multistep biochemical transformations in favor of a desired product using a facile reaction and analytical format. Abstract : A microfluidic device with systematic control over enzyme product yields is demonstrated, where the yield of three products depends on the order of covalently immobilized enzymes along a flowing substrate stream. The device has applications in biochemical synthesis where there is a need for more efficient methods to conduct and analyze multistep enzymatic reactions.